2012
DOI: 10.1159/000341997
|View full text |Cite
|
Sign up to set email alerts
|

Delay Discounting of Reward and Caudate Nucleus Volume in Individuals with α-Synuclein Gene Duplication before and after the Development of Parkinson’s Disease

Abstract: Background/Aims: α-Synuclein (SNCA) may be a key factor in dopaminergic neurotransmission, reward processing, and neurodegeneration in Parkinson’s disease (PD). We investigated delay discounting of reward and caudate volume in SNCA gene duplication carriers before and after the development of PD. Methods: Participants were 7 presymptomatic SNCA duplication carriers who later developed PD (follow-up period: 5.4 years) and 10 matched non-carrier controls. At the follow-up assessment, patients received levodopa (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 77 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…Amemori and Graybiel [] postulate, therefore, that the pACC, in interaction with the striatum, may thus be necessary in “interrelating cognitive and emotional processing to modulate behavior by affecting evaluation of aversive outcome” [Amemori and Graybiel, ; p. 784]. Hence, the self‐seed is selectively associated with reward and value assessment and representation, likely due to its functional connectivity with the striatum [Nakamura et al, ; Szamosi et al, ], which we observed across both MACM and RS.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Amemori and Graybiel [] postulate, therefore, that the pACC, in interaction with the striatum, may thus be necessary in “interrelating cognitive and emotional processing to modulate behavior by affecting evaluation of aversive outcome” [Amemori and Graybiel, ; p. 784]. Hence, the self‐seed is selectively associated with reward and value assessment and representation, likely due to its functional connectivity with the striatum [Nakamura et al, ; Szamosi et al, ], which we observed across both MACM and RS.…”
Section: Discussionmentioning
confidence: 62%
“…784]. Hence, the self-seed is selectively associated with reward and value assessment and representation, likely due to its functional connectivity with the striatum [Nakamura et al, 2012;Szamosi et al, 2013], which we observed across both MACM and RS.…”
Section: Delineating a Conceptual Self-networkmentioning
confidence: 82%
“…Four studies analyzed cognition in carriers of the SNCA gene, and global cognition was assessed in all of them. One of the studies, which included 6 SNCA carriers, found global cognition to be reduced, whereas patients in the other 3 did not show global cognitive decline . A “dysexecutive syndrome” in 3 of the 6 carriers and episodic memory impairment in 1 carrier were also found, although the small sample size limited the significance of this finding…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…One study reported that choice impulsivity was correlated with higher GM density in the putamen, but a lack of comparable studies impeded generalization of this finding. Meanwhile, choice impulsivity was associated with smaller GM volume in the caudate/putamen, but later reports indicated that choice impulsivity is associated with larger GM volume in the caudate/putamen . Tschernegg and colleagues addressed this discrepancy by arguing that, compared with the study by Cho and colleagues, their study included more items to score in the delay‐discounting task, and they averaged discounting scores recorded over repeated sessions to obtain a more stable measure.…”
Section: Evidence From Human Neuroimaging Studiesmentioning
confidence: 99%